2002
DOI: 10.1128/jcm.40.9.3172-3178.2002
|View full text |Cite
|
Sign up to set email alerts
|

groESL Sequence Determination, Phylogenetic Analysis, and Species Differentiation for Viridans Group Streptococci

Abstract: The full-length sequences of the groESL genes (also known as cpn10/60) of Streptococcus anginosus, Streptococcus constellatus, Streptococcus gordonii, and Streptococcus sanguis and the near full-length sequence of the groESL genes of Streptococcus intermedius, Streptococcus bovis, Streptococcus mitis, Streptococcus mutans, Streptococcus oralis, and Streptococcus salivarius were determined. The lengths of the groES genes from the 10 species listed above ranged from 282 to 288 bp, and the full-length sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 29 publications
7
79
0
1
Order By: Relevance
“…As an alternative, sequencing of other housekeeping genes has been used to identify streptococci, e.g., the genes encoding D-alanine:D-alanine ligase (ddl) (19,32,36), glutamate dehydrogenase (gdh) (36,40), the ␤ subunit of RNA polymerase (rpoB) (15), and manganese-dependent superoxide dismutase (sodA) (32,41,42). Likewise, the sequences of the highly variable spacer region between the 16S and 23S rRNA genes and the groESL genes have been used for identification of streptococci (10,48). It is reported that these methods enable reliable identification of Streptococcus isolates to the species level, but they have not been applied to the whole spectrum of Streptococcus species.…”
mentioning
confidence: 99%
“…As an alternative, sequencing of other housekeeping genes has been used to identify streptococci, e.g., the genes encoding D-alanine:D-alanine ligase (ddl) (19,32,36), glutamate dehydrogenase (gdh) (36,40), the ␤ subunit of RNA polymerase (rpoB) (15), and manganese-dependent superoxide dismutase (sodA) (32,41,42). Likewise, the sequences of the highly variable spacer region between the 16S and 23S rRNA genes and the groESL genes have been used for identification of streptococci (10,48). It is reported that these methods enable reliable identification of Streptococcus isolates to the species level, but they have not been applied to the whole spectrum of Streptococcus species.…”
mentioning
confidence: 99%
“…However, it involves more inputs and selection of other genes out of a few thousand genes within the genome is not an easy task. In spite of the fact that around 23 genes have been used frequently in many studies carried out for identifying Streptococcus, no consensus gene has been identified [3,4,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It has also not been realized that except recA, the rest of the 22 genes are not present in all the species of Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus poses a big challenge as most pathogenic strains are genetically very close to each other and have multiple copies of rrs per genome. A few genes which are frequently used for the identification of Streptococcus include genes: cpsA, gdh, groESL, lytA, ply, psaA, pspA, recA, recN, rpoA, rpoB, sodA, tuf, wzg, 16S-23S ribosomal DNA spacer region, and the DNA fragment Spn9802 [3,4,11,[22][23][24][25][26][27][28][29][30][31]. Optochin susceptibility testing (CO 2 atmosphere) in combination with amplification of Spn9802 fragment and the autolysin genes: lytA, rpoB, and tuf, have proved effective in identifying S. pneumoniae [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the microbiota of traditional cheeses in the Mediterranean agro-zones have indicated that enterococci are of a significant importance in cheese ripening and contribute to its typical taste and flavor probably through proteolysis, lipolysis, and citrate breakdown (Felis and Dellaglio, 2007;Manolopoulou et al, 2003). S. thermophilus and other thermophilic streptococci, including E. faecalis ABOU YOUNES,and SHARABI and E. faecium, are among the dominant members of the microflora of many cheeses produced with natural cultures (Teng et al, 2002). Traditional bacterial classification methods based on morphology, physiology and biochemical tests could be time-consuming and misleading (Yanagida et al, 2007).…”
Section: Introductionmentioning
confidence: 99%